Accuracy and precision of non-invasive cardiac output monitoring devices in perioperative medicine: a systematic review and meta-analysis†This Article is accompanied by Editorial Aew442. (March 2017) - Joosten, A; Desebbe, O; Suehiro, K; Murphy, L.S.-L.; Essiet, M; Alexander, B; Fischer, M.-O.; Barvais, L; Van Obbergh, L; Maucort-Boulch, D; Cannesson, M
Abstract: Cardiac output (CO) measurement is crucial for the guidance of therapeutic decisions in critically ill and high-risk surgical patients. Newly developed completely non-invasive CO technologies are commercially available; however, their accuracy and precision have not recently been evaluated in a meta-analysis. We conducted a systematic search using PubMed, Cochrane Library of Clinical Trials, Scopus, and Web of Science to review published data comparing CO measured by bolus thermodilution with commercially available non-invasive technologies including pulse wave transit time, non-invasive pulse contour analysis, thoracic electrical bioimpedance/bioreactance, and CO2 rebreathing. The non-invasive CO technology was considered acceptable if the pooled estimate of percentage error was <30%, as previously recommended. Using a random-effects model, sd, pooled mean bias, and mean percentage error were calculated. An I 2 statistic was also used to evaluate the inter-study heterogeneity. A total of 37 studies (1543 patients) were included. Mean CO of both methods was 4.78 litres min −1 . Bias was presented as the reference method minus the tested methods in 15 studies. Only six studies assessed the random error (repeatability) of the tested device. The overall random-effects pooled bias (limits of agreement) and the percentage error were −0, 13 [−2.38, 2.12] litres min −1 and 47%, respectively. Inter-study sensitivity heterogeneity was high ( I 2 =83%, P <0.001). With a wide percentage error, completely non-invasive CO devices are not interchangeable with bolus thermodilution. Additional studies are warranted to demonstrate their role in improving the quality of care.